Role of Banks in the Commodity Market - Jyoti, (Indian Journal of Finance, 2009)
The development of financial structure is actually an indispensable clause to economic growth. This development is greatly facilitated by the existence of sound financial system which consists of well-developed and integrated financial institutions, innovative instruments and financially deepened market. Amongst all the financial institutions, banking sector has prominently growing and playing a crucial role in the expansion of Indian Financial Market. On the other hand, Commodity trading has been a topical foundation for Indian financial market. It is new opportunity for institutional investors as well. In recent times, Reserve Bank of India has allowed banks to explore the commodity market as an investment avenue within a limited boundary. Banks have taken initiative not only as institutional investors but also as an architect and mediator for the inception and growth of commodity market in India. This paper is an attempt to study the innovative model of commodity market and to analyze the role of banks from different perspectives for the growth of this market in India.